Sistem Pengelolaan Terhadap Pura Tirta Empul Sebagai Daya Tarik Wisata Pusaka Di Tampak Siring Gianyar - Sumaeni, Ni Made; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA, 2018)
The purpose of this study was to determine the management system to Pura Tirta Empul as a tourist attraction in Tampak Siring Gianyar heritage. Background underlying this study is the hallmark and uniqueness of Pura Tirta Empul. The type of data used is qualitative data and quantitative data with the source of primary and secondary data obtained through observation, interview and literature study. Determination of informants using purposife sampling techniques. Analysis of the data used by the process of descriptive qualitative analysis conducted through data reduction, data presentation and conclusions. Management systems to Pura Tirta Empul as a tourist attraction in Tampak Siring Gianyar heritage in this study using POAC management includes planning, organizing, actuating, and controlling. Results from this study is the strength of a leader or manager in executing management functions POAC management system as well as it has been implemented in Pura Tirta Empul. Good management of a positive impact on managers such as the number of tourists is increasing.   Keywords:system management, tourist attraction, heritage tourism